Multidisciplinary team efforts to improve the pregnancy outcome of pregnancy complicated with primary hyperparathyroidism: case series from a single hospital - Hai-ning Jiao; Li-hao Sun; Yan Liu; Jian-qiao Zhou; Xi Chen; Jian-min Liu; Hui-ping Zhong (BMC, 2021)
Abstract Background There is no consensus or management algorithm for primary hyperparathyroidism (PHPT) in pregnancy. Methods This study comprises a retrospective case series. From August 2014 to December 2020, 9 cases of PHPT in pregnancy were diagnosed by a multidisciplinary team (MDT) consultation center of obstetrics in our hospital. Their clinical manifestations, treatment strategies, and maternal and infant outcomes were analyzed. Results The median onset age of the patients was 32 (25 ~ 38) years. PHPT was diagnosed in two cases before pregnancy, in six cases during pregnancy and in one case postpartum. The main clinical manifestations were nausea, vomiting, and other nonspecific symptoms, with anemia as the most common maternal complication. Hypercalcemia crisis was developed in one case. The median levels of preoperative serum calcium and parathyroid hormone (PTH) were 3.08 (2.77 ~ 4.21) mmol/L and 300.40 (108.80 ~ 2603.60) pg/ml, respectively. The parathyroid ultrasonography tests were positive in eight cases and negative in one patient who had an ectopic lesion localized by 99mTc-MIBI. Parathyroidectomy was conducted in 7 cases during the 2nd trimester, including 2 patients diagnosed before pregnancy who refused surgery, 1 patient during the 1st trimester, and 1 patient postpartum, with a significant reduction in serum concentrations of calcium and PTH. A management algorithm was developed. Conclusion This case series suggests that pregnant women with PHPT should be managed by MDT according to the algorithm. If PHPT is confirmed in fertile women before pregnancy, parathyroidectomy should be strongly suggested and performed. If PHPT is diagnosed during pregnancy, even in its mild form, surgical treatment, optimally during the 2nd trimester, is effective and safe for pregnancy and neonatal outcome.